The Health and wellbeing impacts of Home and agile working in Wales: A HIA Approach. (20th October 2021) - Green, L; Ashton, K; Evans, L; Morgan, L; Lewis, R; Azam, S; Bellis, MA
Abstract: The SARS-COV-02 pandemic has globally resulted in a number of policies and interventions to address and reduce the transmission of the disease throughout the population. Mitigation measures have ranged from 'Staying at Home' or 'Lockdowns' to social distancing policies and requirements to work from home when you can. Whilst there are a number of papers which discuss the effects of home or remote working on employees and their families the large scale shift, accelerated pace and wider impacts of such a shift has not been well explored in the literature or has been focussed on specific topics, for example, productivity. HIA is promoted as a beneficial tool to identify the wider impacts of a policy, plan or intervention across a population and as such is well placed to examine and articulate who in a population may be affected and how, and the inequalities that may be created by an intervention such as home working. Using the lens of social determinants and equity focussed-HIA, this work examines the wider impact of home working in Wales during the COVID-19 pandemic. It provides a coherent overview of the major impacts on health and the particular populations affected. It articulates the process followed, the key evidence based findings, discusses the gaps in the evidence base that require further exploration and the impact and influence it has had to date. Finally, it shares the transferable learning, which will be of use to researchers, policy and decision makers, organisations and public health agencies.